Etiologies, outcomes, and prognostic factors of pediatric acute liver failure: A single center’s experience in Turkey - Özçay, Figen; Karadağ-Öncel, Eda; Barış, Zeren; Canan, Oğuz; Moray, Gökhan; Haberal, Mehmet (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Our aim was to determine the etiologies, outcomes, and prognostic indicators in children with acute liver failure. Materials and Methods: Ninety-one patients who were followed for pediatric acute liver failure (PALF) over a 15-year period were included. Patients who survived with supportive therapy were designated as Group 1, while those who died or underwent liver transplantation were designated as Group 2. Results: There were 37 (40.6%) patients in Group 1 (spontaneous recovery) and 54 (59.4%) patients in Group 2. Thirty-two patients (35.2%) underwent liver transplantation. Infectious and indeterminate causes were the most common etiologies (33% each). Among the infectious causes, hepatitis A (76%) was the most frequent. Hepatic encephalopathy grade 3-4 on admission and during follow-up and high Pediatric Risk of Mortality (PRISM) and Pediatric End-Stage Liver Disease (PELD) scores within the first 24 h were related with a poor prognosis. Group 2 had a more prolonged prothrombin time, higher international normalized ratio, more prolonged activated partial thromboplastin time (aPTT), and higher levels of total and direct bilirubin, ammonia, and lactate (for all, p<0.01). Conclusion: Infectious and indeterminate cases constituted the most common etiology of PALF, and the etiology was related to the prognosis in our series. Although high PELD and PRISM scores were related to poor prognoses, no sharp thresholds for individual laboratory tests could be elucidated. Liver transplantation was the only curative treatment for patients with poor prognoses and resulted in high survival rates (1-, 5-, and 10-yearsurvival rates of 81.3%, 81.3%, and 75%, respectively) in our study.